Sarcoidosis Following Rhinoplasty: Report of Four Cases - Ali Faghih Habibi; Shadman Nemati; Pegah Alizadeh; Saman Mikaeeli (Acta Medica Iranica, 2019)
Sarcoidosis is a systemic idiopathic disease, characterized by non-caseating granulomas, primarily affecting the lungs and the lymphatics. Skin involvement is common and lesions may appear in scar tissues. In the present report, four cases of scar sarcoidosis following rhinoplasty are presented which were diagnosed based on serology tests, radiography imaging and histopathology findings. Three women and one man between 32 to 54-year-old are discussed in this report. Skin lesions on their nose were found after an average of 3.8 years of their septorhinoplasty surgeries. Two of the patients had systemic signs such as fever, cough and arthritis. Patients with diagnosed sarcoidosis were treated appropriately. Rhinoplasty is a common procedure today, and the fact that rhinoplasty may lead up to scar sarcoidosis in susceptible people can be an item for surgeons for consideration.